A comunicação do corpo a partir da não visualidade: um estudo teórico-prático - Bellini, Magda Amábile Biazus Carpeggiani (2007)
The main hypothesis of this research is that individuals who carry a congenital visual disability can increase their bodily communication strategies through re-meaningfulness processes of body internal image through movement. For these individuals, a simple level of control, possession, direction, and operation of their bodies become particularly limited, however, it is possible to intervene in this process through specific trainings. The steady and varied proprioceptive stimulation and the vestibular system (concerning equilibrium) can compensate the lack of sight, giving a body sense less precarious. The investigation puts together references from the communication theory and philosophy of mind, demystifying the sight as a singular and unique process. Therefore, it debates the image construction (mainly from Antonio Damásio s work, Lakoff & Johnson and Alain Berthoz) and bodymedia identity (Katz and Greiner). The research results have been tested in practical experiments performed by means of dance classes for blind people since the Master course. Currently, the investigation of some cognition models by cognitive science bias, the survey of disability paradoxical role and its latent connections, have been corroborating that the brain is a highly adaptable and efficient system, able to re-establish communicative links even before the most precarious situations